Optimization of inulin production process parameters using response surface methodology - Wasim Akram (Future Journal of Pharmaceutical Sciences, 2020)
Abstract Background Chicory is one of the major source of inulin. In our study, Box–Behnken model/response surface analysis (RSM) was used for the optimization of spray drying process variables to get the maximum inulin yield from chicory (Cichorium intybus L.). For this investigation, the investigational plan utilized three process variables drying temperature (115–125 °C), creep speed (20–24 rpm), and pressure (0.02–0.04 MPa). Result The optimal variables established by applying the Box–Behnken model were as follows: drying temperature 119.20 °C, creep speed 21.64 rpm, and pressure 0.03 MPa. The obtained powdered inulin by spray drying was investigated for the yield value, identification, size, and surface morphology of the particle. The inulin obtained from the spray drying process consists of a fine molecule-sized white powder. Instead, the drying methods shows a significant effect on the morphology and internal configuration of the powdered inulin, as the inulin obtained from spray drying was of a widespread and uniform size and shape, with a rough surface on increase in temperature and smoother surface while increasing the creep speed. The findings indicate that the spray drying with optimum parameters resulted in maximum product yield. Conclusion The outcomes of the study concluded that the product yield through spray drying technique under optimized condition is optimal as compared to other drying technique. Hence, this technique may be applied at commercial scale for the production of inulin.